Progress and Decline of Legal Thought: Ex-Corruptor as a Legislative Candidate (Analysis of General Election Commission Regulation (PKPU) No. 20/2018) - Damaitu, Emanuel Raja (Universitas Negeri Semarang, 2019)
KPU Regulation Number 20 the Year 2018 is one of the rules that must be adhered to regarding legislative candidates who will be registered as participants in the legislative elections. The KPU regulation was decided by the Supreme Court as a statutory regulation that is not in accordance with the laws and regulations related to the election on it. In fact, normatively, the provisions in the KPU Regulation are in accordance with the rules for the formation of legislation. Normatively, banning legislative candidates who are former prisoners of corruption is a progressive effort from the government to create a government free of corruption. The prohibition does not violate the concept of human rights protection.